Does endometrial receptivity array improve reproductive outcomes in euploid embryo transfer cycles? a systematic review - Mei, Youwen; Wang, Yacong; Ke, Xue; Liang, Xuefei; Lin, Yonghong; Wang, Fang (Frontiers in Endocrinology, 2023)
Besides chromosomal normality, endometrial receptivity is an important factor in determining successful pregnancies. Endometrial receptivity array (ERA), a promising endometrial receptivity test, was speculated to improve the reproductive outcomes. However, its effectiveness is controversial in clinical practice. Therefore, we conducted this review to investigate its role in in vitro fertilization (IVF) treatment. To eliminate the interference of embryo quality, we only analyzed studies that originally reported the reproductive outcomes of patients who underwent ERA-guided euploid embryo transfer (EET).Unexpectedly, it revealed that ERA could not optimize the reproductive outcomes in EET cycles, no matter in general infertile population, or in patients with a history of previous failed embryo transfers.